The Vaginal Microbial Signatures of Preterm Birth Delivery in Indian Women - Kumar, Shakti; Kumari, Naina; Talukdar, Daizee; Kothidar, Akansha; Sarkar, Mousumi; Mehta, Ojasvi; Kshetrapal, Pallavi; Wadhwa, Nitya; Thiruvengadam, Ramachandran; Desiraju, Bapu Koundinya; Nair, G. Balakrish; Bhatnagar, Shinjini; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Background: The incidence of preterm birth (PTB) in India is around 13%. Specific bacterial communities or individual taxon living in the vaginal milieu of pregnant women is a potential risk factor for PTB and may play an important role in its pathophysiology. Besides, bacterial taxa associated with PTB vary across populations. Objective: Conduct a comparative analysis of vaginal microbiome composition and microbial genomic repertoires of women who enrolled in the Interdisciplinary Group for Advanced Research on Birth Outcomes – A DBT India Initiative (GARBH-Ini) pregnancy cohort to identify bacterial taxa associated with term birth (TB) and PTB in Indian women. Methods: Vaginal swabs were collected during all three trimesters from 38 pregnant Indian women who delivered spontaneous term (n=20) and preterm (n=18) neonates. Paired-end sequencing of V3-V4 region of 16S rRNA gene was performed using the metagenomic DNA isolated from vaginal swabs (n=115). Whole genome sequencing of bacterial species associated with birth outcomes was carried out by shotgun method. Lactobacillus species were grown anaerobically in the De Man, Rogosa and Sharpe (MRS) agar culture medium for isolation of genomic DNA and whole genome sequencing. Results: Vaginal microbiome of both term and preterm samples reveals similar alpha diversity indices. However, significantly higher abundance of Lactobacillus iners (p-value All_Trimesters<0.02), Megasphaera sp (p-value1st_Trimester <0.05), Gardnerella vaginalis (p-value2nd_Trimester= 0.01) and Sneathia sanguinegens (p-value2nd_Trimester <0.0001) were identified in preterm samples whereas higher abundance of L. gasseri (p-value3rd_Trimester =0.010) was observed in term samples by Wilcoxon rank-sum test. The relative abundance of L. iners, and Megasphaera sp. were found to be significantly different over time between term and preterm mothers. Analyses of the representative genomes of L. crispatus and L. gasseri indicate presence of secretory transcriptional regulator and several ribosomally synthesized antimicrobial peptides correlated with anti-inflammatory condition in the vagina. These findings indicate protective role of L. crispatus and L. gasseri in reducing the risk of PTB. Conclusion: Our findings indicate that the dominance of specific Lactobacillus species and few other facultative anaerobes are associated with birth outcomes.